Activity pattern of wild fetid in state land forest Merapoh, Pahang - Mat Nafi, Muhammad Izzat Hakimi (2020)
A study to describe the activity pattern of wild felids was carried out in State Land Forest Merapoh Pahang, Malaysia, using camera traps, over a period of 2 months 513 within trap night. 13 camera traps with the brands of six Browning and seven Reconyx were used and setup in Merapoh to get data activity pattern of the wild felids that have in the State Land Forest. With this method, four species of wild cats were detected in the period of this study which is leopard (Panthera Pardus), clouded leopard (Neofelis nebulosa), leopard cat (Prionailurus bengalensis), golden cat (Catopuma temminckii). The use of camera traps provided detailed information on the occurrence and activity patterns of these relatively secretive mammals. All species that have been record by the camera trap is one picture for one species. From the data that have been pool together by the present of the species, the activity pattern of the species has been identifying for each species. This study can be improved by the adding the number of the camera trap, increase the time period of the study and the last one is help form the expert. In conclusion, this study has potential to provide the information of the activity pattern on the wild felids in their nature habitat.